2020
DOI: 10.1021/acsnano.9b09658
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Dispersed Iron–Nitrogen Sites on Hierarchically Mesoporous Carbon Nanotube and Graphene Nanoribbon Networks for CO2 Reduction

Abstract: Atomically dispersed metal and nitrogen co-doped carbon (M-N/C) catalysts hold great promise for electrochemical CO2 conversion. However, there is a lack of cost-effective synthesis approaches to meet the goal of economic mass production of single-atom M-N/C with desirable carbon support architecture for efficient CO2 reduction. Herein, we report facile transformation of commercial carbon nanotube (CNT) into isolated Fe–N4 sites anchored on carbon nanotube and graphene nanoribbon (GNR) networks (Fe-N/CNT@GNR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 59 publications
(100 reference statements)
6
90
0
Order By: Relevance
“…[62] Pan et al reported FeN 4 sites' synthesis on carbon frameworks with graphene nanoribbon attached to the fibrous CNT, achieving high electrochemically active surface area and smooth mass transport. [63] This carbon structure was synthesized through controllable partial unzipping of CNT using KMNO 4 /H 2 SO 4 as oxidants. In contrast, the Fe residues in CNTs synthesized by chemical vapor deposition (CVD) method can be directly used as a Fe source to grow FeN 4 sites.…”
Section: Control the Morphology Of Carbon Substratesmentioning
confidence: 99%
“…[62] Pan et al reported FeN 4 sites' synthesis on carbon frameworks with graphene nanoribbon attached to the fibrous CNT, achieving high electrochemically active surface area and smooth mass transport. [63] This carbon structure was synthesized through controllable partial unzipping of CNT using KMNO 4 /H 2 SO 4 as oxidants. In contrast, the Fe residues in CNTs synthesized by chemical vapor deposition (CVD) method can be directly used as a Fe source to grow FeN 4 sites.…”
Section: Control the Morphology Of Carbon Substratesmentioning
confidence: 99%
“…Having nanotubes as a matrix facilitates mass diffusion and provides good conductivity, which was reflected in the high activity of the catalysts towards the reduction of CO 2 with an FE close to 100% in a wide potential of −0.6 V to −1.0 V vs. RHE, current density of 34.3% at −1.0 V, and stability of 20 h maintaining a percentage of 98% of its initial activity. Pan and co-workers [128] also obtained high electrochemical activity using commercial carbon nanotubes (C-CNT) in the synthesis of the catalysts. C-CNT were oxidized to obtain graphene nanoribbons attached to the outer walls of the remaining nanotubes, which had isolated Fe-N 4 active sites.…”
Section: Smas-n-other Carbon Materialsmentioning
confidence: 99%
“…[ 154–157 ] 5) A series of new photocatalytic systems are developed for CO 2 photoreduction, such as metal organic frameworks (MOFs), [ 158–163 ] covalent organic frameworks (COFs), [ 164–169 ] semiconductor biohybrids systems, [ 170–172 ] and single atom. [ 173–177 ] These systems have different chemical affinities to CO 2 molecules, and thus may change the redox reaction pathways during CO 2 reduction process. Meanwhile, polarity enhancement and creation of spatially separated active sites as new strategies for enhancing charge separation and optimizing reactive catalytic sites attracts intense attentions.…”
Section: Overview Of Photocatalysts For Co2 Reductionmentioning
confidence: 99%